Annual Plan 1968-69 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1968)
In October 1966, the State’s Fourth Plan was finalised after discussions between the State Government and the Planning Commission and an outlay of Rs.926 crores was determined. Since then, however, there have been a number of changes in the economic situation as a result of which the picture of Central and State resources has altered considerably. It is now anticipated that the Fourth Plan outlays determined last year may not be realised and accordingly, recourse has now been taken to the strategy of annual plans framed in the light of resources actually in sight from year to year.
Government of Uttar Pradesh, Planning Department